2020
DOI: 10.3906/biy-2007-85
|View full text |Cite
|
Sign up to set email alerts
|

The inhibitory effect of melatonin on osteoclastogenesis of RAW 264.7 cells in low concentrations of RANKL and MCSF

Abstract: RAW 264.7 cells are one of the most recommended cell lines for investigating the activity and differentiation of osteoclasts. These cells differentiate into osteoclasts in the presence of two critical components: receptor activator of nuclear factor kappa B ligand (RANKL) and macrophage colony stimulating factor (MCSF). Melatonin (MEL) hormone has recently become one of the small molecules used in the field of bone regeneration and bone disease treatment, as it has the ability to inhibit the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A study found that melatonin could inhibit the behavior of osteoclast differentiation, F-actin loop formation, and osteoclast absorption induced by RANKL in vitro in a concentration-dependent manner ( Cutando et al, 2014 ). It has been reported that melatonin could inhibit the differentiation of RAW 264.7 cells into osteoclasts induced by light concentrations of RANKL and MCSF at the cellular level ( Jarrar et al, 2020 ). Moreover, Kim et al indicated that melatonin could inhibit osteoclast differentiation by downregulating the NF-κB pathway and reducing the induction of the NFATc1 transcription factor, though the phosphorylations of ERK, p38, and JNK were not affected.…”
Section: Introductionmentioning
confidence: 99%
“…A study found that melatonin could inhibit the behavior of osteoclast differentiation, F-actin loop formation, and osteoclast absorption induced by RANKL in vitro in a concentration-dependent manner ( Cutando et al, 2014 ). It has been reported that melatonin could inhibit the differentiation of RAW 264.7 cells into osteoclasts induced by light concentrations of RANKL and MCSF at the cellular level ( Jarrar et al, 2020 ). Moreover, Kim et al indicated that melatonin could inhibit osteoclast differentiation by downregulating the NF-κB pathway and reducing the induction of the NFATc1 transcription factor, though the phosphorylations of ERK, p38, and JNK were not affected.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, it was reported that MEL concentrations above 200 µM showed confirmed inhibitory effect on osteoclastogenesis [32]. Besides, we have demonstrated in our previous work that, MEL inhibited the differentiation of RAW 264.7 cells cultured with 10 ng/mL RANKL and 10 ng/mL MCSF in dose-dependent manner and 800 µM was selected as the most efficient anti-osteoclastogenic dose [18].…”
Section: Cell Culture Studiesmentioning
confidence: 80%
“…Loading amounts of BMP-2 and MEL were determined according to the literature and our previous studies, respectively. Our previous study showed that a dose of 800 µM MEL had the best inhibitory effect on the differentiation of RAW 264.7 cells into osteoclasts when the inoculation density was 1 × 10 4 cells/mL [18]. This is why, 300 ng BMP-2 and 186 μg MEL (leads to 800 µM) were embedded, respectively, by the addition of 40 μL of BMP-2 or MEL solution drop by drop with a micropipette into each scaffold.…”
Section: Mel and Bmp-2 Loading And Their In Vitro Release From Chitosan/hap Scaffoldsmentioning
confidence: 99%
“…For comparison, the reported average doubling time of the macrophages used in our study varies from 12 hours to 15 hours, depending on the experimental conditions used (Bancos and Tyner, 2014; Jarrar, Çetin Altindal and Gümüşderelioğlu, 2020). In contrast, our results showed an average doubling time of 22.3 hours, and this figure was consistent with the growth rate measured for the same cells in our lab using standard cell counting procedures.…”
Section: Resultsmentioning
confidence: 99%